Dietary grape pomace – effects on growth performance, intestinal health, blood parameters, and breast muscle myopathies of broiler chickens - Taiwo J. Erinle (Elsevier, 2022)
ABSTRACT: The search for alternatives to antibiotics in poultry production is still on-going and has been directed towards investigation of the efficacy of different potential alternatives. However, it is important that the sought alternatives are cost-efficient and have no negative impact on meat quality, for ease of adoption and profit maximization. This study aimed at exploiting an agro-industrial waste, grape pomace (GP) as an alternative to in-feed antibiotics and assessing the effects on growth, intestinal morphology, ceca microbiota, ceca short-chain fatty acid (SCFA) concentration, blood biochemical parameters, and breast muscle myopathies of broiler chickens. A total of 576 one-day-old Cobb-500 broiler chicks were randomly allotted to 3 dietary treatments – Negative control (NC, a corn-wheat soybean-based diet), NC + 0.05% bacitracin methylene disalicylate (BMD), and NC + 2.5% GP. Each treatment was assigned to 8 replicate pens with 25 birds per pen. Body weight (BW), feed intake (FI), and feed conversion ratio (FCR) were determined weekly. On d 36, 2 chickens/pen were euthanized for measuring blood biochemical parameters, ceca SCFA, and ceca microbiota. White striping (WS) and wooden breast (WB) incidence were assessed in 4 chickens/pen on d 42. The GP diet increased (P < 0.05) average FI throughout the feeding phases compared to the other treatments, but overall FCR was similar. Birds in the GP treatment had higher (P < 0.05) villus height (VH) and increased VH:crypt depth ratio in the duodenum and jejunum compared to other treatments. The level of ceca SCFA and the incidence of WS and WB was the same for all treatments. Plasma Ca and P were significantly higher (P < 0.05) in birds fed GP and BMD, compared to the NC. Birds in the GP treatment had significantly reduced (P < 0.05) plasma aspartate transaminase than other treatments. Birds receiving GP had a higher (P < 0.05) relative abundance of the phylum Bacteroidetes and reduced (P < 0.05) Firmicutes compared to other treatments. The relative abundance of Bacteroides and Lactobacillus genera were higher (P < 0.05) among birds fed GP compared to other treatments. Inclusion of 2.5% GP in broiler chicken diets improved gut morphology and modified the cecal bacterial community and blood biochemical profiles with no adverse effect on growth performance and meat quality.